Short‐ and long‐term survival after adrenalectomy in 53 dogs with pheochromocytomas with or without alpha‐blocker therapy. Issue 3 (9th February 2022) - Enright, Dory; Dickerson, Vanna M.; Grimes, Janet A.; Townsend, Sarah; Thieman Mankin, Kelley M.
Abstract: Objective: To report data related to the short‐ and long‐term survival of dogs undergoing adrenalectomy for pheochromocytoma, and to determine the influence of preoperative alpha‐blocker therapy. Study design: Retrospective. Animals: Fifty‐three dogs. Methods: Medical records were reviewed for dogs diagnosed with pheochromocytoma and treated with adrenalectomy between 2010 and 2020. Preoperative management, imaging studies, intraoperative cardiovascular instability, complications, and procedural information were recorded. When applicable, duration of survival and cause of death, time to recurrence or metastasis, and postoperative complications were recorded. Results: During anesthesia, a hypertensive episode was documented in 46/53 dogs and arrhythmias were recorded in 16/53 dogs. Of these, 37/46 hypertensive dogs and 11/16 dogs with arrhythmias were treated with an alpha‐blocker before surgery. Intraoperative systolic blood pressures reached higher levels by a magnitude of nearly 20% in dogs that were treated preoperatively with an alpha‐blocker ( P  = .01). All dogs survived surgery and 44 survived to discharge. Follow up ranged from 6 to 1653 days (median 450 days). Median survival time for dogs discharged from the hospital was 1169 days (3.2 years). Recurrence and metastasis were suspected in 3 and 8 dogs, respectively. Conclusion: Most dogs survived the immediate postoperative period and achieved long‐term survival with a low reported incidence of tumor recurrence or metastasis. Preoperative alpha‐blocker therapy was not associated with increased survival. Clinical significance: The favorable outcomes reported in this study should be taken into consideration when discussing treatment options for dogs with pheochromocytomas. This study provides no evidence to support preoperative alpha‐blocker therapy.